Monitoring Vertikalitas dan Perubahan Elevasi Gedung di Kota Kupang Menggunakan Metode Leveling Presisi sebagai Upaya Mitigasi Risiko Gempa Bumi: Monitoring Building Verticality And Elevation Changes In Kupang City Using Precision Leveling Methods As An Earthquake Risk Mitigation Strategy - Yacob Victor Hayer; Fabianus J. S. Nope; Marie Mistika Juniarti Alma Bembot; Ambrosius Raha Lelang Wayan (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
This study aims to analyze the results of levelling observations conducted on eleven buildings with various functions, including educational facilities, social and cultural buildings, health facilities, and commercial structures. The observations were carried out to assess levelling values against elevation standards and the vertical condition of the buildings as indicators of structural stability. Based on the analysis, the measurement compliance rate ranged from 73.27% to 100%, with an average of 91.22% and a standard deviation of 9.77%, indicating that the measurement quality is generally good. Most educational buildings recorded levelling values above 90%, while several other buildings showed deviations at specific observation points. The evaluation of physical conditions shows that 63.64% of the buildings are in an upright condition, whereas 36.36% exhibit slight tilting. Although the detected tilt levels are still considered safe, these conditions require periodic monitoring to ensure that no progressive structural settlement occurs. Overall, the study indicates that the structural stability of the buildings within the observation area is relatively good; however, buildings with lower levelling values and slight tilting are recommended for follow-up observations. This research highlights the importance of regular elevation monitoring as part of a Structural Health Monitoring (SHM) system to ensure the safety and service life of buildings.